Eufemisme dan Disfemisme dalam Karangan Emha Ainun Nadjib: “Hidup Itu Harus Pintar Ngegas dan Ngerem” - Habib Rois (Belajar Bahasa, 2021)
Changes in the meaning of words with refinement (euphemism) and refinement (dysfemism) occur at the level of a sentence marked by words, phrases and clauses. The purpose of this research is to describe the forms of euphemisms and dysphemisms in the essay of Emha Ainun Nadjib (Cak Nun) with the title "Life Must Be Clever Ngegas and Ngerem" through a component analysis. The paradigm in research uses qualitative by referring to the natural axioms of reality, the relationship between the researcher and the one being studied, the possibility of generalization, and the causal relationship. The data in this study are in the form of sentences in Cak Nun's essay which are included in the process of changing the meaning of euphemisms and dysfemisms. The data is taken from a book entitled "Life Must Be Smart and Ngerem", an article that contains motivation and teachings of life based on Islamic law. The data analysis process in this study includes four stages, namely domain analysis, taxonomic analysis, component analysis, and cultural theme analysis. The results in this study contain a form of euphemism with two modes of use, namely protection and motivation. Meanwhile, dysphemism has two modes of use which include negative evaluation and satire. The four modes are then combined with the equivalent words in accordance with the context of the sentence, giving rise to comparisons based on the meaning components contained. Comparison of meaning components aims to determine the level of meaning change which refers to refinement and roughing. There is one word without comparing the meaning component with its equivalent, namely the word pramonyet. The term pramonyet is used as a form of curbing which refers to the process of comparing human needs with a monkey.